Thermal taphonomy experiments challenge ultrastructural preservation in the Chengjiang yunnanozoans - He, Kaiyue; Han, Jian; Liu, Jianni; Ou, Qiang; Mussini, Giovanni; Reich, Mike; Shu, Degan (Proceedings of the Royal Society. B, Biological sciences, 2025)
Yunnanozoans from the Chengjiang fossil Lagerstätte (Cambrian Stage 3) are a highly controversial group of fossil deuterostomes. Recent studies have claimed the observation of ultrastructures, including cellular cartilage and microfibrils, in yunnanozoan branchial arches. However, the presence of these micro- to nanoscale details has been questioned on both taphonomic and morphological grounds. Scanning electron microscopy analyses reveal that the organic matter in yunnanozoan gill arches is preserved as homogeneous carbonaceous films, and Raman spectroscopy indicates that these structures were subject to maximum burial temperatures of approximately 261–306°C. To test the likelihood of ultrastructural preservation in yunnanozoan tissues, we conducted thermal taphonomy experiments on amphioxus and living vertebrate cartilages (150–300°C, 48 h), spanning the maximum metamorphic temperatures indicated by Raman spectroscopy (261–306°C) for these Chengjiang macrofossils. Centimetre- to micrometre-scale structures remained visible at 300°C, while cartilage ultrastructures, including the iconic paired, septum-bearing cartilage lacunae and bundles of collagen fibres, were partially preserved at or below 270°C, but were not recognizable at 280°C. Considering the highest temperatures experienced by yunnanozoan fossils over millions of years, these results fail to support the cellular-scale preservation of cartilaginous tissues in the Chengjiang Biota.